The psychological skill characteristics of Indonesian volleyball players reviewed based on gender and position - Pulungan, Khoirul Anwar; Dimyati, Dimyati (Universitas Nusantara PGRI Kediri, 2019)
This study aims to know: (1) the psychological skill characteristics of Indonesian volleyball players reviewed based on gender; (2) the psychological skill characteristics of Indonesian volleyball players reviewed based on position. The type of this study was descriptive quantitative research, using a survey method with a research design: a retrospective causal-comparative. The population in this study was Indonesian volleyball players attending the 18th Asian Games 2018 event in Indonesia numbering 28 Indonesian players, consisting of 14 male and 14 female players, with an average age of 25 years old for males and 20 years old for females. Meanwhile, the data analysis technique used parametric inferential statistics by using the independent t-test for gender difference and one-way Anova for position difference, with a significance level of 0.05. Results show that: (1) there is a significant difference in the psychological skill characteristics of Indonesian volleyball players reviewed based on gender, with the Sig. value 0.007 < 0.05; (2) there is no significant difference in the psychological skill characteristics of Indonesian volleyball players reviewed based on position, with the Sig. value 0.930 > 0.05.